Development of STEM-Based Performance Assessments to Analyze Students' Creativity - Munifatuzzahroh, Ukhti Mutia; Sarwi, Sarwi; Linuwih, Suharto (Physics Communication, 2024)
This research aims to develop a STEM-based performance assessment instrument to analyze students' creativity. This research used the Research and Development method referring to the 4D model. The define stage was carried out by conducting preliminary studies which were then analyzed, starting from analysis of initial, student, concept, task and learning objectives. The design stage was an initial design in the form of Draft I. The development stage was carried out to produce draft II, draft III, and final products from performance assessment instruments. Draft II was obtained through the results of expert validation revisions. Draft III was the result of small-scale product trials. The Final Product was from the results of large-scale product trials. STEM-based performance assessment instruments used to analyze students' creativity were developed in the form of 1) Lesson Plan, 2) Student Worksheets, 3) Grid, 4) Performance Assessment Sheet, 5) Assessment Rubric, and 6) Assessment Guidelines. Expert Validation of STEM-based performance assessment instruments used to analyze students' creativity produced valid criteria that was worthy of trial. Based on the results of product trials, both small-scale and large-scale also showed reliable categories. The developed STEM-based performance assessment instrument is valid and reliable so that it can be used to analyze students' creativity. Based on this, it was known the profile of students' creativity in two Public High Schools of Brebes Regency.